The Global Landscape of EBV-Associated Tumors - Shannon-Lowe, Claire; Rickinson, Alan (Frontiers in Oncology, 2019)
Epstein-Barr virus (EBV), a gamma-1 herpesvirus, is carried as a life-long asymptomatic infection by the great majority of individuals in all human populations. Yet this seemingly innocent virus is aetiologically linked to two pre-malignant lymphoproliferative diseases (LPDs) and up to nine distinct human tumours; collectively these have a huge global impact, being responsible for some 200,000 new cases of cancer arising worldwide each year. EBV replicates in oral epithelium but persists as a latent infection within the B cell system and several of its diseases are indeed of B cell origin; these include B-LPD of the immunocompromised, Hodgkin Lymphoma (HL), Burkitt Lymphoma (BL), Diffuse Large B cell Lymphoma (DLBCL) and two rarer tumours associated with profound immune impairment, plasmablastic lymphoma (PBL) and primary effusion lymphoma (PEL). Surprisingly, the virus is also linked to tumours arising in other cellular niches which, rather than being essential reservoirs of virus persistence in vivo, appear to represent rare cul-de-sacs of latent infection. These non-B cell tumours include LPDs and malignant lymphomas of T or NK cells, nasopharyngeal carcinoma (NPC) and gastric carcinoma of epithelial origin, and leiomyosarcoma, a rare smooth muscle cell tumour of the immunocompromised. Here we describe the main characteristics of these tumours, their distinct epidemiologies, histological features and degrees of EBV association, then consider how their different patterns of EBV latency may reflect the alternative latency programmes through which the virus first colonises and then persists in immunocompetent host. For each tumour, we discuss current understanding of EBV’s role in the oncogenic process, the identity (where known) of host genetic and environmental factors predisposing tumour development, and the recent evidence from cancer genomics identifying somatic changes that either complement or in some cases replace the contribution of the virus. Thereafter we look for possible connections between the pathogenesis of these apparently different malignancies and point to new research areas where insights may be gained.